Journal of a second voyage for the discovery of a north-west passage from the Atlantic to the Pacific : performed in the years 1821-22-23,in His Majesty's ships Fury and Hecla, under the orders of Captain William Edward Parry, R.N., F.R.S., and commander of the expedition. - Parry, William Edward, Sir, 1790-1855. (New York : Published by E. Duyckinck, G. Long, Collins & Co., Collins & Hannay, W.B. Gilley, and H.I. Megarey, 1824)
Mode of access: Internet.